Sustainability indicators and data management for small-scale agricultural systems: the case of water resources - Elena Sánchez-Arnau; Antonia Ferrer-Sapena; Maria Carmen Cárcel-Mas (Regional Environmental Change, 2026)
The management of non-industrial farming sites often lacks context-specific indicators that allow effective planning. Identifying reliable measures suited to small-scale agriculture (especially in settings with unique features such as suburban orchards) is therefore crucial for their viability. In this paper, we systematically review the indicators that can be applied in such contexts and compare them with those used in similar environments. Because the number of possible indices is as wide as the dimensions involved (social, economic, geographical, water, etc.), we narrow our scope to indicators related to sustainability and water resources. By analyzing several published time series, we show that many of these indices are strongly correlated, so tracking just one or two of them is normally sufficient, a simplification that greatly eases management in low-resource settings. We also point out that many variables can be obtained from open-data repositories or other easily accessible sources, so that producers with limited budgets can monitor the most relevant information without investing in costly data-collection systems. The literature suggests that this reduction could likewise apply to other sustainability factors.

Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

Assessing Viral Pollution in Seawater, Using Passive Samplers, Quantitative PCR and Target Enrichment Sequencing - Ignasi Estarlich-Landajo; Maria Tarradas-Alemany; Sandra Martínez-Puchol; Cristina Mejías-Molina; Júlia Verdaguer; Sílvia Bofill-Mas; Marta Rusiñol (Water, Air, & Soil Pollution, 2026)
Detecting pathogenic viruses in seawater presents significant challenges due to their typically low concentrations and the transient nature of contamination events. To address these challenges, this study evaluates passive sampling (PS) as a semiquantitative methodology for viral surveillance in seawater, focusing on human adenovirus (HAdV), norovirus GI (NoVGI) and GII (NoVGII). To optimize the approach, nylon and nitrocellulose membranes were compared, with nylon demonstrating greater consistency and reliability. In Barcelona, across 14 sampling events, 6 of them during combined sewer overflow (CSO) events, PS ( n = 51) was assessed against grab sampling ( n = 21) coupled with ultrafiltration (UF). Using PS, HAdV, NoVGI, and NoVGII were detected in 100%, 62.5%, and 75% of non-CSO events, respectively, outperforming UF, which detected these viruses in only 37.5%, 25%, and 37.5% of the same events. PS was applied during CSO events at both the CSO discharge point and at a nearby bathing site. As expected, the sampler deployed at the discharge point detected higher viral loads of HAdV, NoVGI, and NoVGII. However, viral genomes were also detected at the bathing site. Target enrichment sequencing of seawater vertebrate-infecting viruses conducted on PS samples, identified vertebrate viral pathogens, including members of the Circoviridae , Parvoviridae and Picornaviridae families, showcasing the extensive viral diversity in seawater due to fecal contamination. This study emphasizes the risk of viral exposure when seawater is impacted by CSO and the potential of PS as a robust tool for seawater viral surveillance, offering enhanced sensitivity and utility for quality management and public health risk assessment. Graphical Abstract

Secondary succession in the Caatinga is composed of species that persist throughout all chronosequence - Francisca Soares Araújo; Fernanda Kelly Gomes Silva; Fernando Roberto Martins; Jean-Francois Mas; Marie-Pierre Ledru; Maria Virginia Oliveira Silva; Carlos Eduardo Carvalho; Daniel Pontes Oliveira; Bruno Sousa Menezes (Journal of Arid Environments, 2026)

Phytochemical investigation of Calophyllum sundaicum P.F.Stevens: isolation, structure elucidation, and biological potential - Mas Atikah Lizazman; Vivien Yi Mian Jong; Nor Hisam Zamakshshari; Yiizamy Suffian; Mohamad Izwan Bin Ismail; Enis Nadia Md Yusof; Nurr Maria Ulfa Binti Seruji (Natural Product Research, 2026)

Unveiling lipid and oxylipin composition in the coffee leaves throughout coffee cherry maturation - Maria Cruz Figueroa-Espinoza; Daniel Guzmán-Rosales; Lindsay Mas-Normand; Claire Vigor; Thierry Durand; Camille Oger; Jean-Marie Galano; Valerie Gros; Guillaume Reversat; Jorge Maldonado-Veneroso; Oscar González-Ríos; Mirna L. Suárez-Quiroz; et al. (Food Chemistry, 2025)

Pig slurry valorization by ammonia recovery, biogas upgrading and microbial protein production - Amanda Prado de Nicolás; Andreu Serra-Toro; Maria Ventura; Sergi Astals; Joan Dosta; Francesc Mas; Yolanda Segura; Juan A. Melero; Fernando Martínez; Daniel Puyol (Bioresource Technology, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Molecular docking studies and in-vitro cholinesterase inhibitory activities of chemical constituents of Calophyllum gracilentum - Nurr Maria Ulfa Seruji; Vivien Yi Mian Jong; Thiruventhan Karunakaran; Nor Hisam Zamakshshari; Siau Hui Mah; Natalie Vivien Gunter; Mas Atikah Lizazman; Arai Masayoshi (Phytochemistry Letters, 2024)

Everything's not lost: Caatinga areas under chronic disturbances still have well-preserved plant communities - Maria Soraya Macêdo; Bruno Sousa Menezes; Marie Pierre Ledru; Jean-François Mas; Fernanda Kelly Gomes Silva; Carlos Eduardo Carvalho; Rafael Carvalho Costa; Roberta Boscaini Zandavalli; Arlete Aparecida Soares; Francisca Soares Araújo (Journal of Arid Environments, 2024)

Shoot and biomass reduction of perennial weeds using hydromulches and physical changes in the mulches - Maria Teresa Mas; Antoni Maria Claret Verdú; Gabriel Pardo; Jorge Pueyo; Josep Claramunt; Alicia Cirujeda (Journal of Plant Diseases and Protection, 2024)

Ammoniacal nitrogen recovery from swine slurry using a gas-permeable membrane: pH control strategies and feed-to-trapping volume ratio - Andreu Serra-Toro; Yasmina Ben Hammou Abboud; Maria Alicia Cardete-Garcia; Sergi Astals; Francesco Valentino; Francesc Mas; Joan Dosta (Environmental Science and Pollution Research, 2024)
Gas-permeable membrane (GPM) technology is gaining interest to recover nitrogen from residual effluents due to its effectiveness, simple operation and capacity of producing a nutrient rich product with fertilising value. In this study, a GPM contactor was used at 25 °C to recover total ammoniacal nitrogen (TAN) from swine slurry as a concentrated (NH 4 ) 2 SO 4 solution. Firstly, a synthetic solution was tested on a wide pH range (6–12). Results showed that the ammonia mass transfer constants ( K m ) increased from 7.9·10 −9 to 1.2·10 −6 m/s as the pH increased. The reagent consumption to control the pH per mole nitrogen recovered had a minimum at pH 9, which showed a K m value of 3.0·10 −7 m/s. Secondly, various pH control strategies were tested using swine slurry, including (i) no pH control, (ii) pH control at 8.5, 9.0 and 10.0, and (iii) an initial spike of the NaOH equivalent to the required to control the pH at 9. The test without pH control reached a TAN recovery of around 60%, which could be an interesting strategy when high nitrogen recoveries or short operating times are not required. The pH control at 9 stood out as the most favourable operating condition due to its high K m and lower reagent consumption. Thirdly, several feed-to-trapping volume ratios ranging from 1:1 to 15:1 were tested using swine slurry at pH 9. These assays revealed that a GPM process with a high feed-to-trapping volume ratio fastens the recovery of 99% of TAN as a high purity (NH 4 ) 2 SO 4 solution containing 40 g N/L.

Late Paleolithic hunter-gatherers’ resilience in the face of the transformation of the vegetation landscape and climate change in the Pre-Pyrenees - Bàrbara Mas; Xavier Mangado; Marta Sánchez de la Torre; José-Miguel Tejero; Josep Maria Fullola; Ethel Allué (Quaternary Science Reviews, 2023)

Reappraising the use of forearm rings for bat species - Lourdes Lobato-Bailón; Adrià López-Baucells; David Guixé; Carles Flaquer; Jordi Camprodon; Xavier Florensa-Rius; Maria Mas; Laura Torrent; Laura Ordeix; Oriol Tallo-Parra; Maria P. Ribas; Ignasi Marco; et al. (Biological Conservation, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Innovation facilitators and sustainable development: a country comparative approach - Nuria Chaparro-Banegas; Ana Maria Ibañez Escribano; Alicia Mas-Tur; Norat Roig-Tierno (Environment, Development and Sustainability, 2023)
National and international organizations have introduced policies aimed at sustainable development. These policies are designed to encourage sustainable forms of business to meet the Sustainable Development Goals (SDGs) of the 2030 Agenda. Regional inequalities in sustainable development may be exacerbated by disparate levels of innovation. This paper analyzes the variations between clusters of countries according to the degree to which they have achieved the SDGs and their levels of innovation facilitators. Two types of analyses were employed. First, cluster analysis was used to examine changes in groups of regions with similar innovation characteristics between 2015 and 2020. Data for 122 countries were gathered from the World Bank, the SDG Index, and the Global Innovation Index. Second, multiple linear regression analysis was used to assess the power of the variables in the model to explain the level of sustainable development. The results reveal four clusters (low, medium, high, and very high innovative facilitators and sustainable development), as well as movements between those clusters from 2015 to 2020. The multiple linear regression analysis shows that the variables have explanatory power with respect to the dependent variable of sustainable development. This analysis also reveals different degrees of importance of the variables for each cluster. The findings highlight the need to consider the limitations of economic growth in terms of innovation facilitators to promote sustainable development. If policymakers recognize the limitations of economic growth and the physical ecosystem, degradation of the environment can be avoided, even when there is innovation. Global and individual social welfare can thus be ensured. This study offers valuable insights into how to achieve sustainable development through innovation facilitators by providing in-depth knowledge of the individual characteristics of innovation systems and considering the limitations of economic growth.

A cryptic variation in a member of the Ovate Family Proteins is underlying the melon fruit shape QTL fsqs8.1 - Cecilia Martínez-Martínez; Maria José Gonzalo; Pablo Sipowicz; Manuel Campos; Irene Martínez-Fernández; Carmen Leida; Mohammed Zouine; Konstantinos G. Alexiou; Jordi Garcia-Mas; María Dolores Gómez; Pablo Tornero; Miguel Ángel Pérez-Amador; et al. (Theoretical and Applied Genetics, 2022)
Key message The gene underlying the melon fruit shape QTL fsqs8.1 is a member of the Ovate Family Proteins. Variation in fruit morphology is caused by changes in gene expression likely due to a cryptic structural variation in this locus. Abstract Melon cultivars have a wide range of fruit morphologies. Quantitative trait loci (QTL) have been identified underlying such diversity. This research focuses on the fruit shape QTL fsqs8.1 , previously detected in a cross between the accession PI 124112 (CALC, producing elongated fruit) and the cultivar ‘Piel de Sapo’ (PS, producing oval fruit). The CALC fsqs8.1 allele induced round fruit shape, being responsible for the transgressive segregation for this trait observed in that population. In fact, the introgression line CALC8-1, carrying the fsqs8.1 locus from CALC into the PS genetic background, produced perfect round fruit. Following a map-based cloning approach, we found that the gene underlying fsqs8.1 is a member of the Ovate Family Proteins (OFP), CmOFP13, likely a homologue of AtOFP1 and SlOFP20 from Arabidopsis thaliana and tomato, respectively. The induction of the round shape was due to the higher expression of the CALC allele at the early ovary development stage. The fsqs8.1 locus showed an important structural variation, being CmOFP13 surrounded by two deletions in the CALC genome. The deletions are present at very low frequency in melon germplasm. Deletions and single nucleotide polymorphisms in the fsqs8.1 locus could not be not associated with variation in fruit shape among different melon accessions, what indicates that other genetic factors should be involved to induce the CALC fsqs8.1 allele effects. Therefore, fsqs8.1 is an example of a cryptic variation that alters gene expression, likely due to structural variation, resulting in phenotypic changes in melon fruit morphology.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Buffalo Infection by Fasciola gigantica Transmitted by Radix acuminata in Uttar Pradesh, India: A Molecular Tool to Improve Snail Vector Epidemiology Assessments and Control Surveillance - Kumari Sunita; Santiago Mas-Coma; Maria Dolores Bargues; Sadaf; Mohammad Aasif Khan; Maria Habib; Saad Mustafa; Syed Akhtar Husain (Acta Parasitologica, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Bat echolocation plasticity in allopatry: a call for caution in acoustic identification of Pipistrellus sp. - Cecilia Montauban; Maria Mas; Carme Tuneu-Corral; Owen S. Wangensteen; Ivana Budinski; Joan Martí-Carreras; Carles Flaquer; Xavier Puig-Montserrat; Adrià López-Baucells (Behavioral Ecology and Sociobiology, 2021)
Animals modify their behaviours and interactions in response to changing environments. In bats, environmental adaptations are reflected in echolocation signalling that is used for navigation, foraging and communication. However, the extent and drivers of echolocation plasticity are not fully understood, hindering our identification of bat species with ultrasonic detectors, particularly for cryptic species with similar echolocation calls. We used a combination of DNA barcoding, intensive trapping, roost and emergence surveys and acoustic recording to study a widespread European cryptic species complex ( Pipistrellus pipistrellus and Pipistrellus pygmaeus ) to investigate whether sibling bat species could exhibit extreme echolocation plasticity in response to certain environmental conditions or behaviours. We found that P. pygmaeus occupied the acoustic niche of their absent congeneric species, producing calls with P. pipistrellus ’ characteristic structure and peak frequencies and resulting in false positive acoustic records of that species. Echolocation frequency was significantly affected by the density of bats and by maternity rearing stage, with lower frequency calls emitted when there was a high density of flying bats, and by mothers while juveniles were non-volant. During roost emergence, 29% of calls had peak frequencies typical of P. pipistrellus , with calls as low as 44 kHz, lower than ever documented. We show that automatic and manual call classifiers fail to account for echolocation plasticity, misidentifying P. pygmaeus as P. pipistrellus . Our study raises a vital limitation of using only acoustic sampling in areas with high densities of a single species of a cryptic species pair, with important implications for bat monitoring. Significance statement Ultrasonic acoustic detectors are widely used in bat research to establish species inventories and monitor species activity through identification of echolocation calls, enabling new methods to study and understand this elusive understudied group of nocturnal mammals. However, echolocation call signalling in bats is intrinsically different to that of other taxa, serving a main function of navigation and foraging. This study demonstrates an extreme level of plasticity, showing large variation in call frequency and structure in different situations. We showcase the difficulty and limitation in using acoustic sampling alone for bat monitoring and the complications of setting parameters for species identification for manual and automatic call classifiers. Our observations of call frequency variation correlated with density and absence of congenerics provide novel insights of behavioural echolocation plasticity in bats.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Recurring fires in Mediterranean habitats and their impact on bats - Adrià López-Baucells; Carles Flaquer; Maria Mas; Pere Pons; Xavier Puig-Montserrat (Biodiversity and Conservation, 2021)

Fonsecaea pedrosoi Conidia Induces Activation of Dendritic Cells and Increases CD11c+ Cells in Regional Lymph Nodes During Experimental Chromoblastomycosis - Telma Fátima Emidio Kimura; Lavínia Maria Dal’Mas Romera; Sandro Rogério de Almeida (Mycopathologia, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Bat boxes and climate change: testing the risk of over-heating in the Mediterranean region - Garazi Martin Bideguren; Adrià López-Baucells; Xavier Puig-Montserrat; Maria Mas; Xavier Porres; Carles Flaquer (Biodiversity and Conservation, 2019)

Dispositional use of emotion regulation strategies and resting-state cortico-limbic functional connectivity - Maria Picó-Pérez; Pino Alonso; Oren Contreras-Rodríguez; Ignacio Martínez-Zalacaín; Clara López-Solà; Susana Jiménez-Murcia; Antonio Verdejo-García; José M. Menchón; Carles Soriano-Mas (Brain Imaging and Behavior, 2018)

Brain alterations in low-frequency fluctuations across multiple bands in obsessive compulsive disorder - Mònica Giménez; Andrés Guinea-Izquierdo; Victoria Villalta-Gil; Ignacio Martínez-Zalacaín; Cinto Segalàs; Marta Subirà; Eva Real; Jesús Pujol; Ben J Harrison; Josep Maria Haro; Joao R Sato; Marcelo Q Hoexter; et al. (Brain Imaging and Behavior, 2017)

The Critical Role of Notch1–TLR 4 Signaling in the Inflammatory and Fungicidal Activity of Macrophages Against Paracoccidioides brasiliensis Strain Pb18 - Lavínia Maria Dal’Mas Romera; Gilberto Hideo Kaihami; Grasielle Pereira Jannuzzi; José Roberto Fogaça de Almeida; Sandro Rogério de Almeida (Mycopathologia, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Bat boxes in urban non-native forests: a popular practice that should be reconsidered - Adrià López-Baucells; Xavier Puig-Montserrat; Ignasi Torre; Lídia Freixas; Maria Mas; Antoni Arrizabalaga; Carles Flaquer (Urban Ecosystems, 2017)

Hardpan in skeletal soils: Statistical approach to determine its depth in a cherry orchard plot - Ramon Josa; Marta Ginovart; Maria Teresa Mas; Antoni M. C. Verdú (Biologia, 2015)

Prevalence of potentially thermophilic microorganisms in biofilms from greenhouse-enclosed drip irrigation systems - Olga Sánchez; Isabel Ferrera; Laura Garrido; Maria del Mar Gómez-Ramos; Amadeo Rodríguez Fernández-Alba; Jordi Mas (Archives of Microbiology, 2014)

Combined Therapy with Idebenone and Deferiprone in Patients with Friedreich’s Ataxia - Daniel Velasco-Sánchez; Asuncion Aracil; Raquel Montero; Ana Mas; Lorenzo Jiménez; Mar O’Callaghan; Maria Tondo; Antoni Capdevila; Josep Blanch; Rafael Artuch; Mercedes Pineda (The Cerebellum, 2011)

Quantification of Human Adenoviruses in European Recreational Waters - Sílvia Bofill-Mas; Byron Calgua; Pilar Clemente-Casares; Giuseppina La Rosa; Marcello Iaconelli; Michele Muscillo; Saskia Rutjes; Ana Maria de Roda Husman; Andreas Grunert; Ingeburg Gräber; Marco Verani; Annalaura Carducci; et al. (Food and Environmental Virology, 2010)